Fracture and fatigue life of Al-based MMCs machined at different conditions. (15th March 2018) - Pramanik, A.; Basak, A.K.
Highlights: Fatigue cracks don't follow machining traces. The course and nature of cracks depend on the reinforcement size. Fractured surfaces are very similar regardless of particles size and machining conditions. The larger particles reduce the fatigue life at all interacting parameters. Abstract: This study investigates fracture and fatigue performance of metal matric composites (MMCs) without any reinforcement and, 0.7 and 13 µm particle (10 vol%) reinforced which were machined at different feeds and speeds. Fractured surface as well as fatigue generated cracks were investigated in details. The effect of interactions among input machining parameters with their variations on fatigue life has also been analysed. It was found that fatigue cracks don't follow machining traces. Moreover, the cracks are almost straight and sharp when reinforcing particles are smaller but change the course, and surface along the crake is highly damaged when the reinforced particles are bigger. The appearance of fractured surfaces of the samples are very similar regardless of particles size and machining conditions. Though compressive residual stress is generated on the machined MMC surfaces, fatigue life of MMCs are much shorter than that of corresponding matrix material due to the fracture and detachment of reinforcing particles from matrix. Fatigue life has an initial decreasing trend with the rise of feed-rate and then it increases significantly with further increase of feed-rate in the absence of particles machine at low speed. However, fatigue life remains almost constant with the increase of feed-rate for larger particle reinforced MMC machined at high speed. With the increase of speed, opposite trends on fatigue life were noticed for MMCs and matrix material when machined at low and high feeds, respectively. The larger reinforced particles reduces the fatigue life of machined specimens at every interacting combinations of parameters.